LncRNA GHET1 Promotes Hypoxia-Induced Glycolysis, Proliferation, and Invasion in Triple-Negative Breast Cancer Through the Hippo/YAP Signaling Pathway - Wang, Yu; Liu, Shuwei (Frontiers in Cell and Developmental Biology, 2021)
Objective: This study seeks to obtain data which help to assess the specific impacts and mechanism of lncRNA GHET1 in the development of triple-negative breast cancer (TNBC). Methods: qRT-PCR-based analysis of lncRNA GHET1 expression in TNBC tissues and adjacent healthy tissues was first applied, and its expression was then measured at cellular level, including TNBC cells and human normal breast epithelial cell line MCF10A. On completion of transfection of negative shRNA or lncRNA GHET1 shRNA, the TNBC cells, HCC1937 and MDA-MB-468, were then cultured in normoxia or hypoxia environment, respectively. 5-ethynyl-2 '-deoxyuridine (EdU) assay, colony formation assay, and transwell assay was applicable to the determination of cell proliferation, cell viability, and invasion in each group, respectively. Reagent kits were for testing glucose consumption and lactate production levels. HCC1937 cells with knockdown or overexpression of lncRNA GHET1 were injected into the nude mice, followed by examination of resulting tumor volume and weight. Distribution and expression of Hippo/YAP signaling pathway-related proteins were probed using western blotting. Results: Highly expressed lncRNA GHET1 in TNBC tissues and cells, and induction of lncRNA GHET1 by hypoxia were proved. Knockdown of lncRNA GHET1 significantly reduced proliferation, viability and invasion of TNBC cells, decreased glucose consumption and lactate production levels, and significantly inhibited tumor development. Knockdown of lncRNA GHET1 increased phosphorylation levels of LATS1 and Yes-associated protein (YAP) to retain YAP within the cytoplasm, while overexpression of lncRNA GHET1 or hypoxia promoted nuclear translocation of YAP and TNBC development. Conclusion: LncRNA GHET1 expression can be induced by hypoxia, which leading to excessive activation of Hippo/YAP signaling pathway, thus promoting TNBC progression.